Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s11240-007-9228-1
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated transformation of sorghum (Sorghum bicolor (L.) Moench) using an improved in vitro regeneration system

Abstract: An improved regeneration protocol suitable for transformation of sorghum was developed. The improvements focused on limiting the production of phenolic compounds and the use of suitable culture vessels for each developmental stage in plant regeneration from immature embryo derived calli. The addition of activated charcoal in the callus induction medium reduced the production of black pigments, however it also inhibited the callus formation on immature embryo explants. Cold pre-treatment of the immature seeds f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 27 publications
(28 reference statements)
0
44
0
Order By: Relevance
“…A total of 15 transgenic plants were produced from 300 initial IEs (5% frequency) and confirmed by Southern blot (Nguyen et al, 2007). The TF could be enhanced from 2.6% to 7.6% by heating the IEs of cultivar P898012 at 43°C for 3 min with cooling at 25°C prior to the Agrobacterium infection (Gurel et al, 2009).…”
Section: Sorghum (Sorghum Sp)mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 15 transgenic plants were produced from 300 initial IEs (5% frequency) and confirmed by Southern blot (Nguyen et al, 2007). The TF could be enhanced from 2.6% to 7.6% by heating the IEs of cultivar P898012 at 43°C for 3 min with cooling at 25°C prior to the Agrobacterium infection (Gurel et al, 2009).…”
Section: Sorghum (Sorghum Sp)mentioning
confidence: 99%
“…Callus formation from IEs of the Sorghum bicolor cultivar Sensako 85/1191 could be improved when the embryos (1.0-1.2 mm) were dissected from immature seeds pretreated at 4°C for one day (Nguyen et al, 2007). A total of 15 transgenic plants were produced from 300 initial IEs (5% frequency) and confirmed by Southern blot (Nguyen et al, 2007).…”
Section: Sorghum (Sorghum Sp)mentioning
confidence: 99%
“…In sorghum, like most monocotyledonous plants, in vitro culture regimes are primarily somatic embryogenesis based systems (Elkonin and Pakhomova 2000;Jogeswar et al 2007; Kaeppler and Pedersen 1996;Pola et al 2008;Pola and Mani 2006;Sato et al 2004a). As per the second component of plant transformation, integration of genetic elements, sorghum has been successfully transformed using both direct DNA delivery methods (Battraw and Hall 1991) and Agrobacterium-mediated transformation protocols (Cai et al 2002;Gao et al 2005a, b;Gurel et al 2009;Howe et al 2006;Nguyen et al 2007;Zhao et al 2000). While both DNA delivery systems are proven technologies for recovery of stable sorghum transformants, more laboratories are moving towards implementing the latter due to the tendency of Agrobacteriummediated transformants to carry lower copy number insertions and/or have a higher frequency of coexpression of the nonselected transgenic cassette (Dai et al 2001;Gao et al 2008;Zhao et al 1998).…”
Section: Sorghum Transformationmentioning
confidence: 99%
“…Phenolics are produced during the in vitro culturing of sorghum immature embryos, but the production of these secondary metabolites is enhanced upon inoculation with A. tumefaciens. To alleviate the negative effects of phenolics on sorghum transformation media supplements such as polyvinylpolypyrrolidone (PVPP) (Cai et al 1987), and elevation of potassium phosphate levels (Elkonin and Pakhomova 2000;Sato et al 2004a), or the exposure of explants to reduced temperature (Nguyen et al 2007) have been shown to be able to reduce, but not totally eliminate the negative impact of these compounds. Triggering of the plant's defense response upon challenge with A. tumefaciens may lead not only to the production of secondary metabolites, but also to cell death, which can further hamper the efficiency of recovery of transgenic plants.…”
Section: Sorghum Transformationmentioning
confidence: 99%
“…Since the earliest 90's, laboratories around the world have generated improvements in sorghum regeneration and transformation that are ensuing in more consistent protocols. Transgenic sorghum plants have been generated via biolistic (Casas et al, 1993;Casas et al, 1997;Zhu et al, 1998;Able et al, 2001;Emani et al, 2002;Jeoung et al, 2002;Devi and Sticklen, 2003;Tadesse et al, 2003;Girijashankar et al, 2005) or Agrobacterium mediated transformation (Zhao et al, 2000;Carvalho et al, 2004;Gao et al, 2005;Howe et al, 2006;Van Nguyen et al, 2007;Nguyen et al, 2007;Gurel et al, 2009;Lu et al 2009;Mall et al, 2011).…”
Section: Introductionmentioning
confidence: 99%